The Social Cognitive Theory by Albert Bandura and its Implementation in Arabic Language Learning - Athiyah Laila Hijriyah; Annindita Hartono Putri; Agung Setiyawan; Aleeya Humaira Badrisya (Mantiqu Tayr: Journal of Arabic Language, 2024)
Arabic language learning in Indonesia can experience significant improvement if, in its implementation, there is a role for learning models, reinforcement and motivation, information processing, and students' self-confidence when speaking Arabic. This research aims to analyze Bandura's social cognitive thinking and its implementation in the Arabic language context. This research approach is a descriptive qualitative analysis study with the type of library research. The main source of data comes from various documents in books and scientific articles. Data collection is carried out through documentation techniques, namely tracing data sources that have been written and sources that are directly related to the figures being researched, and analysis using the content analysis method. Test the validity of the data using the credibility test method (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results of the research show that Bandura's social cognitive theory can be applied in Arabic language learning by improving the presentation of material through hiwar, imitation of material that has been studied, habituation, creating a language environment, maximizing learning media, and increasing students' motivation to use Arabic on a daily basis. The advantages of implementing Bandura's social cognitive theory in learning Arabic are prioritizing maharah istima' and maharah kalam, using a variety of learning media, increasing learning motivation, and creating a conducive learning atmosphere. The weakness is that learning evaluation is only based on the results, not the process, and requires sufficient time and effort to implement. Bandura's social cognitive thinking made a major contribution to the Arabic language, namely in developing interactive language learning methods and media, improving Arabic language skills, and increasing learner motivation and self-confidence. From this research, further research can be developed related to the implementation of social cognition in different cultural contexts, its effectiveness, and how the environment influences Arabic language learners.